Could Parental Vaccine Hesitancy in Childhood Immunization Programs Increase After COVID-19 Vaccines? - Mehmet Semih Demirtaş (Ahi Evran Medical Journal)
The effective success of the vaccines combating diseases played a significant role in the initiation and expansion of national/global childhood vaccines programs. Vaccine hesitancy is an important issue affecting public health that can be influenced by many factors such as confidence, social media interaction and convenience. Vaccine hesitancy should be taken seriously, not only by pediatricians and other health professionals, but also by governments and health policy makers. Governments, relevant public institutions and NGOs need to take an active role in informing the public about childhood immunization, and in setting/implementing policies to reduce and prevent risks associated with vaccine hesitancy. Removing false and inaccurate information about vaccination from social media and the internet can be achieved through collaboration between governments, the technology sector, health professionals and civil society organizations.